Edward Dixon papers - Dixon, Edward
Ledgers, daybooks, journal, waste books, blacksmith accounts, volume containing receipts and two letters, and a mathematics exercise book relating chiefly to Dixon's business and financial transactions in Port Royal, Caroline County, Va. Subjects include tobacco trade and plantations in Virginia and trade with Great Britain. Ledgers document Dixon's work as an agent for trading companies in England and Scotland and include accounts of John Younger and Glassford and Company. Ships referenced in the ledgers include the Friendship. Some ledgers also contain accounts relating to Dixon's personal financial affairs and include both lists and birth registers of slaves owned by Dixon and his sons.
Individuals represented include Jonathan Boucher, John Boutwell, John Catlett, William Fitzhugh, Robert Gilchrist, James Jameson, Richard Henry Lee, John Micou, Edmund Pendleton, Thomas M. Randolph, William Taliaferro, James Taylor, John Tennant, and Dixon's father-in-law, Thomas Turner.
Also available on microfilm
Microfilm produced from originals in the Manuscript Division.
Merchant, of Port Royal, Caroline County, Va.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Boucher, Jonathan, -- 1738-1804.; Boutwell, John; Catlett, John; Fitzhugh, William, -- 1741-1809.; Gilchrist, Robert, -- of Virginia; Jameson, James; Lee, Richard Henry, -- 1732-1794.; Micou, John; Pendleton, Edmund, -- 1721-1803.; Randolph, Thomas M. -- 1768-1828.; Taliaferro, William; Taylor, James, -- 1769-1848.; Tennant, John, -- of Virginia; Turner, Thomas, -- -approximately 1757.; Younger, John; Friendship (Ship); Glassford and Company; Blacksmithing -- Virginia -- 18th century; Mathematics -- Study and teaching -- 18th century; Merchants -- Virginia -- Port Royal; Merchants -- Virginia -- Caroline County; Plantations -- Virginia; Slavery -- Virginia -- Caroline County; Tobacco industry -- Virginia; Great Britain -- Commerce -- History -- 18th century; Great Britain -- Commerce -- Virginia; Virginia -- Commerce; Virginia -- Commerce -- Great Britain; Virginia -- History; Merchants